A new water stable zinc metal organic framework as an electrode material for hydrazine sensing. (27th June 2018) - Sohail, Manzar; Altaf, Muhammad; Baig, Nadeem; Jamil, Rabia; Sher, Muhammad; Fazal, Atif
Abstract : Metal–organic frameworks (MOFs) as direct electrode materials for electrochemical sensing can offer inherent advantages such as containing sensing element and redox mediator in a single molecule. Abstract : Metal–organic frameworks (MOFs) are an emerging class of materials exhibiting high surface areas, controlled pore sizes, open metal sites and organic linkers. Utilizing MOFs as direct electrode materials for electrochemical sensing can offer inherent advantages such as containing a sensing element and a redox mediator in a single molecule; however, the direct use of MOFs as electrode materials is hindered because of their insulating nature and less stability in an aqueous medium. In this study, a new water stable Zn-MOF was synthesized and used directly as an electrode material. The Zn-MOF possesses good ability to electrocatalyze the hydrazine oxidation reaction. The Zn-MOF's inherent poor conductivity was overcome by including a hydrophobic electrolyte, tetrakis(4-chlorophenyl)borate tetradodecylammonium salt (ETH 500), during the fabrication of the Zn-MOF membrane. After coating a thin film of the nafion-ETH500 supported Zn-MOF over a glassy carbon electrode (GCE), the response for hydrazine oxidation was substantially improved. Linear sweep voltammetry (LSV) demonstrated a wide linear range from 20 to 350 μM ( R 2 = 0.9922) for hydrazine. A detection limit of 2 μM ( n = 3) was observed. The electrochemical behavior of the ZnMOF/ETH500/nafion modified GCE revealed that MOFs have a promising future as electrode materials for direct electrochemical sensing.